« Le jardin aux sentiers qui bifurquent » (Borges) - Frédérique Calcagno-Tristant (Communication)
The adventure narrative of multimedia resembles a "garden of many winding paths", but it incontestably returns the spectator/actor to the author. The narrative and the aesthetics are thus subject to a veritable author strategy. This intentional drive to impute multimedia texts to an author at any price goes on from a particular proceeding of rhetoric : the misdemeanor of the initiate, the symbolic of play, and the process of virtualization as of a light show. This analysis also allows for a reassessment, from the angle of pluridisciplinarity (semiology of the image, film narrativology, and psychoanalysis), of concepts such as, interactivity, the symbolic and the virtual.